Offensive Depictions of the Prophet Muhammad (PBUH) and Muslim Response - A. Z. Hilali (Formad English Foundation NTB Jakarta, 2026)
The Crusade is an iconic event in history, and violent clashes between Muslims and Christians are still continue in different parts of Europe. In this regard, Western media along with some arrogant people, are playing a central role in provoking the situation towards an unending crisis. The wave of anti-Muslim sentiment and Islamophobia is prevalent in various forms, and media is portraying Islam as a violent religion and Muslims as arrogant or terrorists. Scholars define this moment as the rise of Islamophobia and Xenophobic against Muslims. The controversies and provocations became more severe when the Western media published depictions of Prophet Muhammad (PBUH), along with the display of historical artwork. Although it was a longstanding tradition within Islam and Christianity to publish or redraw the pictures of prophets. In contemporary times, Muslims perceive this as offensive. This action not only hurt but also provoked the Muslims around the world. They claimed that visual depictions of the prophets should be prohibited and are particularly averse to visual representations of Prophet Muhammad (PBUH). In this context, the key concern is with newspapers, i.e Charlie Hebdo and Jyllands-Posten, which used the images and encouraged idolatry, whereas Islam does not permit depictions of Prophet Muhammad. So, this analysis comprises the work of Western and Muslim scholars and also includes moderate views about the depiction. Nonetheless, there is a need to promote the notion of coexistence based on mutual respect and without that, peace and harmony cannot prevail, which is the beauty of all religions.